PEMBINGKAIAN PEMBERITAAN APARTEMEN CIKARANG DI â€œXYZ.COMâ€ DAN â€œABCD.COMâ€ - Ine Anggraini (Jurnal Komunikasi dan Bisnis, 2019)
Project development is undertaken by Lippo Group currently has licensing issues such as Environmental Impact Analysis and Building Permit. This turned out to be an agenda deemed important by the mass media to be known by the public. What is in the mass media will affect the subjective reality of social interaction. This study aims to examine the coverage of XYZ.com and ABCD.com in presenting news about the construction of apartments in Cikarang namely "Apart". This study also seeks to explain the comparison of reality constructions carried out by XYZ.com and ABCD.com. This study uses a constructivist paradigm with a qualitative approach. Data analysis in this study used Pan and Kosicki. The results showed that framing XYZ.com on the problem of the construction of this apartment tends to favor the developer and blame the deputy governor of West Java. The element of media ownership is very influential. Meanwhile, ABCD.com supports the construction of Aparta. However, ABCD.com is very careful in conveying the facts and trying to invite readers to see the real reality that private developers should not be obstructed by their permission to participate in development in the regions.Â Keywords: Cikarang Apartment, Pan and Kosicki Framing, XYZ.com, ABCD.com